Sprint performance following plyometric conditioning activity in elite sprinters - Michał KRZYSZTOFIK; Mateusz JOPEK; Dariusz MROCZEK; Aleksander MATUSIŃSKI; Adam ZAJĄC (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Considering the significance of the ankle joint for sprinting with the spring-like properties of the Achilles tendon, it seems that plyometric activating exercises could significantly potentiate maximum velocity sprinting. Therefore, the objective of this study was to evaluate the effects of specific plyometric exercises engaging the ankle joint, called stiff-legged hops as a conditioning activity (CA) on countermovement jump (CMJ) and sprinting performance evaluated over a distance of 50m in elite female and male sprinters that differ in athletics level. Material and methods: Thirty-two sprinters of the Polish National Team were assigned into experimental and control (CTRL) groups, while the experimental group was further equally divided by the 50m sprint time (ELITE; S-ELITE). All participants performed pre-CA (5 min before) and post-CA (5 and 10 min after CA) CMJ and 50m sprints. The CA consists of 3 sets of 10 repetitions of stiff-legged hops, while the CTRL group did not perform any activity. Results: The stiff-legged hops had no significant effect on either CMJ or the 50 m sprint performance in both the ELITE and S-ELITE athletes. However, there was a significant increase in 20 m (p = 0.025; η2 = 0.162) and 30 m sprint time (p = 0.02; η2 = 0.172), with an increase in ground reaction time (p = 0.009; η2 = 0.211) in post-CA from pre-CA with no difference between the groups. The use of stiff-legged hops as a pre-sprint CA did not provide noticeable benefits or drawbacks in CMJ and 50 m sprinting among elite sprinters. However, it may even deteriorate 20 and 30 m performed due to increased ground reaction time. Conclusion: The results of this research do not provide evidence that supports the use of such CA in training or pre-competition contexts.